Seasonality of the Agulhas Current with respect to near- and far-field winds - Hutchinson, Katherine (Marine Research (MA-RE) Institute, 2018)
The Agulhas Current plays a critical role in both local and global ocean circulation and climate regulation, yet the mechanisms that determine the seasonal cycle of the current remain poorly understood. Model studies predict an austral winter-spring maximum in poleward volume transport, whilst observations reveal an austral summertime (February-March) maximum. Here, the role of winds on Agulhas Current seasonality is investigated using shallow water models, satellite measurements, and a 23-year transport proxy based on observations. A one-and-a-half layer reduced gravity model is shown to successfully reproduce the seasonal phasing of the current. This seasonality is found to be highly sensitive to the propagation speed of Rossby waves, which determines the arrival time of the wind stress signal at the western boundary. By matching Rossby wave speeds to those observed using altimetry, an Agulhas Current with a maximum flow in February and a minimum flow in July is simulated, agreeing well with observations. Near-field winds, to the west of 35◦E, dominate this seasonality, as signals from more remote wind forcing dissipate due to destructive interference while crossing the basin. Local winds driving coastal upwelling/downwelling directly over the Agulhas cannot, alone, account for the observed seasonal phasing, as they force a NovemberDecember maximum and June minimum in flow. The seasonal response to Indian Ocean winds is also investigated using a barotropic (single layer) model with realistic topography. A barotropic adjustment cannot explain the observed Agulhas Current seasonality, predicting a wintertime maximum in transport. The results from the barotropic simulation are similar to previous model studies, where seasonality is dominated by a southward propagation of signals via the Mozambique Channel, suggesting that these models are too barotopic in their response to the winds. Findings from this study elucidate the role of near-field winds and baroclinic processes in determining the seasonality of the Agulhas Current.